Kondisi Sosial Ekonomi Masyarakat Korban Bencana Gempa Bumi di Hunian Tetap Kelurahan Tondo Kecamatan Mantikulore Kota Palu - Hdayat, Ahsan; Arsy, Risma Fadhila (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
This study aims to determine the socio-economic conditions of the victims of the earthquake in the permanent residence of Tondo Village, Mantikulore District, Palu City. The method used is descriptive qualitative, with 4 research subjects. Data collection techniques by observation, interviews, and documentation. The research instrument used interview guidelines. The data analysis used is interactive model data analysis. The results showed that; The results of the research can be concluded as follows: 1) earthquake disaster is a big problem in Indonesia, especially for the people of Palu City; 2) the natural conditions and spatial planning of housing affect the social interaction of the Tondo permanent resident community; 3) the researcher sees the social process in two aspects, namely mutual assistance and mutual assistance. People still rarely do gotong royong in the community; 4) the people of the Tondo sub-district, most of their main jobs as traders are as clerks and employees. People's income is included in the middle-income group and low-income group; 5) the government provides a house to live in for the community. The house provided by the government has a land area of ​​10 x 20 meters and a building area of ​​6 x 8 meters which has been facilitated by water, electricity, and bathrooms; 6) the people of the Tondo sub-district receive assistance in the form of an Indonesian Smart Card; 7) In addition to the KIP, the Government also provides a Healthy Indonesia Card for the community (KIS).